Neighborhood Satisfaction in Modern and Old Neighborhoods in Ýstanbul - Emine Ümran Topçu (European Regional Science Association (ERSA), 2005)
There is growing interest among academics and policy makers in both Turkey and abroad to monitor social progress. As a result of this, much activity is focused on measuring quality of neighborhood life, via the development and implementation of subjective indicators. Neighborhood satisfaction would appear prima facie to be a more appropriate variable to use as a measure of the overall quality of neighborhood life. This paper undertakes a case of satisfaction on the Anatolian side of Ýstanbul.The objective of the paper is to determine how the characteristics of a neighborhood influence quality of life in a traditional locale. A second objective of this paper is how to develop and use quality of life indicators to achieve a healthier and more sustainable community. Finding out who is most satisfied with the neighborhoods should provide policy makers with information on where to target neighborhood improvements. In this paper , a regression model of an individual neighborhood satisfaction is developed by using data from a 2002 survey, neighborhood satisfaction being used as the dependent variable.
Keywords: 330